Proses Pemesinan Pada Track Frame Excavator di PT. Perkasa Heavyndo Engineering - Dhafa Nurrahiim; Rizal Hanifi (Peneliti.net, 2023)
Currently Indonesia is incessantly in infrastructure development, the use of heavy equipment is certainly very important role in this development. One of the heavy equipment that plays an important role in the construction process is the excavator. Excavator is one type of heavy equipment that has a very important function and role for construction work. In its use, one of the most vital parts in the excavator component is the trackframe, because this section functions as the excavator wheel frame. In this study, the method used was direct observation at the workplace, as well as interacting with workers related to research. In the process of machining the workpiece, several stages are carried out, namely: (1) The process of checking the dimensions of the workpiece by aligning it with what is stated in the technical drawings (2) Qualification of the machine, preparation of tools, and setting up the program on the machine (3) Ensuring the machine operator uses appropriate PPE according to SOP (4) Machining process (5) Process of checking the quality of machining workpieces. And lastly, if everything feels good the overall result then the track frame will be sent back to the client. The machining process carried out on the workpiece consists of milling, drilling and taping, with the machines used are milling machines and drilling machines with a CNC system.